PERLINDUNGAN SAKSI DAN KORBAN PERKOSAAN DENGAN KEKERASAN - Sugiman Sugiman (UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA, 2016)
The criminal act of rape is an unlawful act with violence against women to satisfy the sexual needs of men, taken alone or in groups. On the occasion or circumstances that can not be determined women are objects that can be a victim and perpetrator or victim-witness . The negative impact of rape can be felt lifelong psychological and psychic targanggu . Victims of rape with violence as an essential ingredient to uncover a criminal act is being experienced by the victim and also takes courage both physically and spiritually , the full support of the family , and the support of the parties , especially the government . Juridical protection of witnesses and victims stipulated in Law No. 13 of 2006 jo Law No. 31 of 2014 on the Protection of Witnesses and Victims .